Biological role of NK cells and immunotherapeutic approaches in breast cancer - Roberti, María P.; Mordoh, José; Levy, Estrella M. (Frontiers in Immunology, 2012)
In recent decades, tumor surveillance by the immune system and its impact on disease outcomes in cancer patients in general and in breast cancer (BC) patients in particular has been documented. Natural killer (NK) cells are central components of the innate immunity and existing data indicate that they play a role in preventing and controlling tumor growth and metastasis. Their biological significance was first recognized by their ability to exert direct cellular cytotoxicity without prior sensitization. This is important in tumors, as transforming events are likely to result in downregulation of self-ligands and expression of stress-induced ligands which can be recognized by NK cells. Their activation also leads to secretion of stimulatory cytokines which participate in cancer elimination by several direct mechanisms as well as by stimulating the adaptive immune system. In this regard, it was recently revealed a dendritic cell (DC)-NK cell crosstalk which provides another novel pathway linking innate and adaptive immunity. In addition, NK cells are feasible targets of stimulation in immunotherapeutic approaches such as antibody-based strategies and adoptive cell transfer. Nevertheless, NK cells display impaired functionality and capability to infiltrate tumors in BC patients. This review compiles information about NK cell biology in BC and the attempts which aim to manipulate them in novel therapeutic approaches in this pathology.